DNA from Lactobacillus paragasseri SBT2055 Activates Plasmacytoid Dendritic Cells and Induces IFN-α via TLR9 - Eiji Kobatake; Toshinobu Arai (Microorganisms, 2025)
Previously, we reported that Lactobacillus paragasseri SBT2055 (LG2055) activates plasmacytoid dendritic cells (pDCs) and induces interferon alpha (IFN-α) in vitro. Our clinical trial suggested that LG2055 intake may enhance pDC activity, supporting immune maintenance and reducing subjective common cold symptoms. However, the precise mechanisms remain unclear. In this study, we investigated how LG2055 engages with pDCs to stimulate IFN-α production. We evaluated LG2055-induced pDC activation using flow cytometry, ELISA, and phagocytosis assays. Human peripheral blood mononuclear cells (PBMCs) were stimulated with LG2055 and its components to evaluate immune responses. An in vitro M cell model was used to examine LG2055 translocation. We found that DNA extracted from LG2055 activated pDCs and enhanced IFN-α production via Toll-like receptor 9 (TLR9). Phagocytosis assays demonstrated that LG2055 DNA was internalized by PBMC-derived pDCs, enabling TLR9-mediated signaling. Additionally, LG2055 translocated across M cells in vitro, suggesting potential transport into Peyer’s patches, where it may interact with pDCs. These findings demonstrate that intestinal LG2055 can translocate across M cells, interact with pDCs, and exert immune-stimulatory effects to enhance host antiviral immunity. This study provides mechanistic insight into how dietary components support immune health and could inform the development of novel functional foods or therapeutic strategies.